Nitrogen retention and ammonia production on tungsten. (24th November 2021) - Ghiorghiu, F.; Aissou, T.; Minissale, M.; Angot, T.; De Temmerman, G.; Bisson, R.
Abstract: We report a systematic study that quantifies nitrogen retention and ammonia production on tungsten and that sheds light on the mechanism for ammonia formation on ITER's divertor material. Saturation of the nitrogen-implanted layer in polycrystalline tungsten is observed at room temperature for a nitrogen ion fluence in the low 10 21 N + m −2 range. Nitrogen desorption from this N-implanted layer occurs in the 800–1100 K temperature range and exhibits a zero-order kinetics with an activation energy of 1.45 eV and a prefactor of 5 × 10 24 m −2 s −1 . Following nitrogen and deuterium co-implantation, deuterated ammonia production is observed during temperature programmed desorption between 350 K and 650 K in conjunction with deuterium desorption. In contrast, nitrogen desorption still occurs above 800 K. Significant production of ammonia is obtained only when the nitrogen layer created by ion implantation is approaching saturation and the amount of nitrogen lost to ammonia production is only in the percent range. This result is understood by repeating cycles of deuterium implantation and thermo-desorption below the desorption temperature of the nitrogen layer. The exponential decay of the amount of produced ammonia with cycle number demonstrates that nitrogen diffusion to the surface is negligible in the ammonia production temperature range and that ammonia formation occurs at the outermost surface layer. The maximum quantity of ammonia produced from the present N implanted layer is below 2 × 10 18 ND3 m −2, which is limited by the nitrogen atom surface density. Surface vibrational spectroscopy demonstrates the presence of ammonia precursors on the nitrogen-implanted tungsten surface upon deuterium implantation. These ammonia precursors can be created also at room temperature through the dissociative chemisorption of thermal D2 catalysed by nitrogen present at the tungsten surface and, more efficiently, by adsorption of deuterium atoms.